O ensino de ciências da natureza e de matemática em Curso Técnico Integrado para Jovens e Adultos : concepções e ações da formação - Pedrosa, Eliane Maria Pinto (2015)
This is a doctoral thesis in which leaned to understand the concepts and actions that have sustained the teaching of natural sciences and mathematics, and the challenges of integrated training under the assumption integrated curriculum, formally expressed to the courses Integrated Technical medium / PROEJA. The grasp concepts and actions of Natural Science and Mathematics Education, Ongoing Integrated Technical / PROEJA refers to consider that this is a subject of investigation in that cross different fields of study, since each brings the contributions of its reference to enrich the investigative process developed. Bring as mainstay for the theoretical dialogues with the captured information of research subjects, contributions in the field of adult education and PROEJA, Curriculum, Curriculum Integrated in the context of labor relations and education and teaching of Natural Sciences and Mathematics. Developed a qualitative research, narrative mode seeking to understand through reports, the stories reported by the subjects they teach / teaching experience in these fields of knowledge, in the singular context of the Technical Course in Integrated Electrical / PROEJA, the IFMA, Campus St. Louis / Monte Castelo. Through semi-structured interviews collected empirical material at the four (4) teachers who teach subjects Chemistry, Biology, Physics and Mathematics and the teacher (1) of the course. With eight (8) students selected to have satisfactory attendance and to have availability to participate, I used the technique of focal group, making room for that in the use of speech in debate, everyone could talk about their experiences in teaching in the fields of investigated knowledge. I used the diary to enrich and expand the research data. The empirical material constructed along the research was analyzed rigorously by discursive textual analysis. Recurrences and singularities seized in the narratives of the subjects in junction with the research problem to explain the thesis gave rise to three categories of analysis, namely: Collective Planning and Continuing Education: possibilities and limits of a route start; PROEJA and Integrated Curriculum: similarities and differences; Teaching / Experiencing Teaching of Natural Sciences and Mathematics: potential and contradições. The results show conceptions and actions that approach and distance themselves from the assumptions, principles and fundamentals of the proposed integrated training in an integrated curriculum. The concepts of collective planning and continuing education as key processes to enable possibilities that direct the formation announced are expressed. The design of Science and school subjects of Natural Sciences and Mathematics in a non-positivist view manifests itself. The student as a subject that has knowledge and experience that should be used in the teaching process is evidenced. On the other hand, express yourself insufficient time-spaces formally institutionalized in the work day to collective planning and continuing education. Part of integrative perspectives actions are dependent initiatives and individual determinations.